Targeting Cellular and Tissue HIV Reservoirs With Toll-Like Receptor Agonists - Macedo, Amanda B.; Novis, Camille L.; Bosque, Alberto (Frontiers in Immunology, 2019)
The elimination of both cellular and tissue latent reservoirs is a challenge toward a successful HIV cure. “Shock and Kill” are among the therapeutic strategies that have been more extensively studied to target these reservoirs. These strategies are aimed towards the reactivation of the latent reservoir using a latency-reversal agent (LRA) with the subsequent killing of the reactivated cell either by the cytotoxic arm of the immune system, including NK and CD8 T cells, or by viral cytopathic mechanisms. Numerous LRAs are currently being investigated in vitro, ex vivo as well as in vivo for their ability to reactivate and reduce latent reservoirs. Among those, several toll-like receptor (TLR) agonists have been shown to reactivate latent HIV. In humans, there are 10 TLRs that recognize different pathogen-associated molecular patterns. TLRs are present in several cell types, including CD4 T cells, the cell compartment that harbors the majority of the latent reservoir. Besides their ability to reactivate latent HIV, TLR agonists also increase immune activation and promote an antiviral response. These combined properties make TLR agonists unique among the different LRAs characterized to date. Additionally, some of these agonists have shown promise towards finding an HIV cure in animal models. When in combination with broadly neutralizing antibodies, TLR-7 agonists have shown to impact the SIV latent reservoir and delay viral rebound. Moreover, there are FDA-approved TLR agonists that are currently being investigated for cancer therapy and other diseases. All these has prompted clinical trials using TLR agonists either alone or in combination towards HIV eradication approaches. In this review, we provide an extensive characterization of the state-of-the-art of the use of TLR agonists towards HIV eradication strategies and the mechanism behind how TLR agonists target both cellular and tissue HIV reservoirs.